2009
DOI: 10.1161/strokeaha.109.555144
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Stroke Mortality by Smoking and Age at Menopause Among Korean Postmenopausal Women

Abstract: Background and Purpose-The association between body mass index and mortality caused by subtypes of stroke among postmenopausal women in terms of smoking status and age at menopause remains controversial. Methods-The data were derived from a cohort study of 3321 with 17.8 years of follow-up (1985 to 2002). Hazard ratios (HRs) and 95% CIs for strokes as related to body mass index were estimated by Cox proportional hazard models adjusted for age, hypertension, smoking, drinking, occupation, education, self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…The association between stroke mortality and overweight has been less studied. Recently, in both Caucasian men and Asian women, overweight was independently associated with a greater risk of stroke death [32,33] . An independent association was also demonstrated between BMI and stroke mortality [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The association between stroke mortality and overweight has been less studied. Recently, in both Caucasian men and Asian women, overweight was independently associated with a greater risk of stroke death [32,33] . An independent association was also demonstrated between BMI and stroke mortality [3] .…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, a study among Korean menopausal women revealed an increased risks of total stroke mortality and hemorrhagic stroke mortality with increasing BMI, particularly in those women with early menopause and those who smoked. 12 These discrepancies to the former data may be due to dietary, geographic, or lifestyle differences between Asian and Western populations, 11 whereas gender differences 12 and of course ethnic variances may play also a role.…”
Section: Body Weight and Stroke: Before And After The Eventmentioning
confidence: 96%
“…Besides the aforementioned statistical concerns, it is unclear if lower BMI was a result of healthy living, medical or psychiatric illness, malnutrition, neglect, lower socioeconomic status, or drug abuse. Of note, two Asian population studies 13,14 did not demonstrate the obesity paradox; the differences in incidence of obesity, lifestyle, and diet may lessen the contribution of corpulence as a risk factor for initial strokes and hence its subsequent "protective" effect. Immobilized limbs after an infarct lose bone mineral density, muscle area, and gain in intramuscular fat with changes possibly accelerating with age.…”
mentioning
confidence: 99%